A critical evaluation of differential display as a tool to identify genes involved in legume nodulation: looking back and looking forward - Lievens, Sam (Oxford University Press, 2001)
Screening for differentially expressed genes is a straightforward approach to study the molecular basis of a biological system. In the last 10 years, differential screening technology has evolved rapidly and currently high-throughput tools for genome-wide transcript profiling, such as expressed sequence tags and microarray analysis, are becoming widely available. Here, an overview of this (r)evolution is given with emphasis on the differential display method, which for many years has been the preferred technique of scientists in diverse fields of research. Differential display has also been the method of choice for the identification of genes involved in the symbiotic interaction between Azorhizobium caulinodans and Sesbania rostrata. The advantages with respect to tissue specificity of this particular model system for legume nodulation and the results of a screening for early nodulation-related genes have been considered in the context of transcriptome analyses in other rhizobium–legume interactions.